Use of medicinal plants by the elderly in Lagoa Seca, Paraíba, Brazil - Jerônimo, Rayane Ellen de Oliveira (2019)
Medicinal plants have been part of the history of mankind since the beginning, having therapeutic, curative and preventive action against numerous diseases. This knowledge was passed on between generations, with the elderly being the ones with the greatest knowledge and practices with medicinal plants. However, its improper use may represent health risks, especially for the elderly. Therefore, the objective of this study was to carry out a research with an ethnobotanical approach with elderly students from the Open University at Maturity University of the State University of Paraíba, in the municipality of Lagoa Seca - PB. At first, an interview was conducted with 27 elderly people through a semi-structured questionnaire, with questions about their profile and the use of medicinal plants, followed by lectures on the use of medicinal plants, ways of cultivation and preparation. Of the elderly, 85.15% were women and 14.81% men, with ages ranging from 61 to 87 years. Regarding the use of medicinal plants, the most cited were teas (66.66%) and compresses (18.51%). Regarding effectiveness, 92.59% stated that they obtained good results with the use of plants and 7.40% were not satisfied with the result. Most of the elderly students at the Open University at Maturity in the city of Lagoa Seca - PB, use medicinal plants to treat diseases, with rosemary for bone problems, chamomile for high blood pressure and fennel for insomnia. They are very interested in the safe and rational use of medicinal plants, indicating the importance of educational actions on this topic.